Impact of Compensation, Productivity, and Service Quality on Member Satisfaction: A Study on Eccindo Cooperative: Dampak Kompensasi, Produktivitas, dan Kualitas Layanan terhadap Kepuasan Anggota: Studi pada Koperasi Eccindo - Rizdatul Umah; Herlinda Maya Kumalasari (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the influence of compensation, productivity, and service quality on member satisfaction within the Eccindo Cooperative. Employing a quantitative approach, a purposive sampling method was used to select 75 respondents among the cooperative's members. Data were collected through questionnaires, and multiple linear regression analysis was employed for data analysis using SPSS 20. The results provide empirical evidence that compensation, productivity, and service quality each individually influence member satisfaction. Furthermore, the study reveals that these factors collectively have a significant impact on member satisfaction. These findings contribute to our understanding of the key determinants of member satisfaction in cooperative organizations and have implications for enhancing member loyalty and cooperative performance.Highlights : This study examines the influence of compensation, productivity, and service quality on member satisfaction in the context of the Eccindo Cooperative. Utilizing a quantitative approach and purposive sampling, data was collected from 75 cooperative members through questionnaires. Multiple linear regression analysis in SPSS 20 confirms that compensation, productivity, and service quality individually impact member satisfaction, and collectively, these factors significantly contribute to member satisfaction, offering insights into enhancing member loyalty and cooperative performance. Keywords: Compensation, Productivity, Service Quality, Member Satisfaction, Eccindo Cooperative